PEMBACAAN AWAL TERHADAP PUISI DAN FOTO DALAM BUKU FOTO JAKARTA ESTETIKA BANAL SEBAGAI SEBUAH CATATAN PERJALANAN - Arif Furqan (POETIKA, 2015)
This paper aims to report the reading attempt of a photobook as a new form of travel account. The photobook mentioned is a book rich with visual narration and also enclose few literary texts in form of poem. With the challenge of the photobook form, I will regard the book as a travel account and elaborate the author’s technique in ‘writing’ his travel account.Keywords: Photo, Photobook, Poem, Travel Account